Sex, Culture and Modernity in China - Dikötter, Frank (Book collections on Project MUSE., 1995)
With the disintegration of Confucian cosmology after the fall of the imperial system in China, medical science was introduced as a foundation for social order. This study traces the emergence of new sexual identities in this period.